ChemInform Abstract: Tandem Synthesis and in vitro Antiplasmodial Evaluation of New Naphtho[2, 1‐d]thiazole Derivatives. Issue 4 (31st January 2013) - Cohen, Anita; Verhaeghe, Pierre; Crozet, Maxime D.; Hutter, Sebastien; Rathelot, Pascal; Vanelle, Patrice; Azas, Nadine
Abstract Derivatives (IIIb) and (Vb) exhibit an encouraging in vitro antiplasmodial activity on the K1 multi‐resistant P.